2017
DOI: 10.1002/chem.201702728
|View full text |Cite
|
Sign up to set email alerts
|

Transition and Alkali Metal Complex Ternary Amides for Ammonia Synthesis and Decomposition

Abstract: A new complex ternary amide, Rb [Mn(NH ) ], which simultaneously contains both transition and alkali metal catalytic sites, is developed. This is in line with the recently reported TM-LiH composite catalysts, which have been shown to effectively break the scaling relations and achieve ammonia synthesis under mild conditions. Rb [Mn(NH ) ] can be facilely synthesized by mechanochemical reaction at room temperature. It exhibits two temperature-dependent polymorphs, that is, a low-temperature orthorhombic and a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
1
24
1
3
Order By: Relevance
“…They both exhibited a significant activity increase over the best performing ternary nitride catalyst, which was Co 3 Mo 3 N, with activities of 11 mmol g −1 h −1 for K 2 [Mn(NH 2 ) 4 ], 6 mmol g −1 h −1 for Rb 2 [Mn(NH 2 ) 4 ], and 5.3 mmol g −1 h −1 for Co 3 Mo 3 N, all of which were measured at 400 °C and 1 MPa. [ 145,149 ] This increase in activity was also reported at a much‐reduced pressure, with the ternary amides tested at 1 MPa compared to 10 MPa for Co 3 Mo 3 N. Along with the results highlighted in the previous section where an increase in activity is noted when the support material for a Ru catalyst is changed from hydride to amide (CaH 2 to Ca(NH 2 ) 2 ), [ 105,116 ] this move from ternary nitrides to ternary amides may be the key next step in this class of catalysts.…”
Section: Metal Nitride Catalystssupporting
confidence: 59%
See 1 more Smart Citation
“…They both exhibited a significant activity increase over the best performing ternary nitride catalyst, which was Co 3 Mo 3 N, with activities of 11 mmol g −1 h −1 for K 2 [Mn(NH 2 ) 4 ], 6 mmol g −1 h −1 for Rb 2 [Mn(NH 2 ) 4 ], and 5.3 mmol g −1 h −1 for Co 3 Mo 3 N, all of which were measured at 400 °C and 1 MPa. [ 145,149 ] This increase in activity was also reported at a much‐reduced pressure, with the ternary amides tested at 1 MPa compared to 10 MPa for Co 3 Mo 3 N. Along with the results highlighted in the previous section where an increase in activity is noted when the support material for a Ru catalyst is changed from hydride to amide (CaH 2 to Ca(NH 2 ) 2 ), [ 105,116 ] this move from ternary nitrides to ternary amides may be the key next step in this class of catalysts.…”
Section: Metal Nitride Catalystssupporting
confidence: 59%
“…Alongside the ternary nitrides that are highlighted in Table 6, Cao et al [ 149 ] have reported on ternary amides of transition and alkali metals. Both Rb 2 [Mn(NH 2 ) 4 ] and K 2 [Mn(NH 2 ) 4 ] were synthesized through ball milling the respective metals at room temperature under 0.7 MPa of NH 3 .…”
Section: Metal Nitride Catalystsmentioning
confidence: 99%
“…Although the active phases are composed of TM and hydrides, amide and/or imide were often observed as intermediate species during the catalysis. Ternary amides of Rb 2 Mn(NH 2 ) 4 and K 2 Mn(NH 2 ) 4 , which contain transition metal Mn and Rb/K in one phase, were also demonstrated highly catalytically functional for ammonia synthesis …”
Section: Complex Hydrides For Catalysismentioning
confidence: 99%
“…[12][13][14] Lithium imide based catalysts have shown comparable or superior performance to state-of-the-art ruthenium catalysts. [15][16][17][18] In this context, in situ neutron powder diffraction experiments indicated that the lithium imide becomes nonstoichiometric under operating conditions, with a mixed amide-imide composition dependent on the temperature and conversion. 15 Isotope exchange experiments have confirmed that this variable composition allows for bulk nitrogen and hydrogen exchange between the catalyst and ammonia.…”
Section: Introductionmentioning
confidence: 99%